2002
DOI: 10.1093/brain/awf007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 potently induces Leão’s cortical spreading depression in vivo in the rat

Abstract: According to the 'neuronal' theory, cortical spreading depression (CSD) is the pathophysiological correlate of migrainous aura. However, the 'vascular' theory has implicated altered vascular function in the induction of aura symptoms. The possibility of a vascular origin of aura symptoms is supported, e.g. by the clinical observation that cerebral angiography frequently provokes migrainous aura. This suggests that endothelial irritation may somehow initiate one of the pathways resulting in migrainous aura. Up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
175
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 50 publications
10
175
0
3
Order By: Relevance
“…This is observed in animals in the brain topical model of the vasoconstrictor ET-1 for example [55,70,71], or in response to microemboli [72].…”
Section: Spreading Ischemiamentioning
confidence: 96%
See 1 more Smart Citation
“…This is observed in animals in the brain topical model of the vasoconstrictor ET-1 for example [55,70,71], or in response to microemboli [72].…”
Section: Spreading Ischemiamentioning
confidence: 96%
“…In the late 1990s, the inverse neurovascular coupling mechanism was found in rats that may be a pathophysiological correlate of migrainous stroke and mechanism for ischemic lesion progression [54,67,68,90]. Different animal models evolved that reconciled the so-called 'vascular theory of the migraine aura' by Wolff [91] with the spreading depression theory of migraine aura by Leão and Morison [4], such as the brain topical model of the vasoconstrictor endothelin-1 (ET-1) [55,70], or the microembolus model [72] in which mild ischemia induces spreading depolarizations with almost similar patterns to that of spreading depolarizations in healthy tissue. Moreover, it was found that cerebral microangiopathies such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy are associated with both higher incidence of migraine with aura in patients [92] and lower electrical and potassium threshold for spreading depolarizations in the animal model [93].…”
Section: A Brief History Of Spreading Depolarizationmentioning
confidence: 99%
“…They were prepared and tested as described previously from double-barrelled theta-glass capillaries (Fa. H. Kugelstätter, Garching, Germany; Dreier et al, 2002). Up to three electrodes were inserted into the suprasylvian and marginal gyri, with one located within 1 mm of the microdialysis probe.…”
Section: Direct Current (And K + ) Microelectrodesmentioning
confidence: 99%
“…One such vascular change that has been suggested in patients with migraine with aura is a Ôspreading oligaemiaÕ (Olesen et al, 1981;Dreier et al, 2001). Dreier et al (2002) have suggested that the link between the vascular oligaemia and the neurological spreading depression may be that endothelial irritation triggers cortical spreading depression. Hadjikhani et al (2001) showed vasoconstriction and then vasodilation followed the cortical spreading depression using an imaging study.…”
Section: Pathophysiology Of Migrainementioning
confidence: 99%